2016
DOI: 10.4084/mjhid.2016.005
|View full text |Cite
|
Sign up to set email alerts
|

Features of Adolescents Tuberculosis at a Referral Tb's Hospital in Tehran, Iran

Abstract: ObjectiveTo identify the pattern of the clinical, radiological, diagnostic procedures and loss to follow-up of the diagnosed cases of active tuberculosis (TB) adolescents.MethodsThis study was a retrospective analysis of the medical records of 143 adolescents aged 10 to 18 years with tuberculosis who were admitted TB wards of National Research Institute of Tuberculosis and Lung Disease (NRITLD) in Tehran, Iran, between March 2006 and March 2011.ResultsOf the 143 patients identified, 62.9% were females. Median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
3
10
2
Order By: Relevance
“…Table 1 shows the major sites of disease and prevalence of confirmed disease in case series of adolescents with tuberculosis identified during this review. 10-12, [14][15][16][17][18][19][20][21][22][23][24] While peripheral (most commonly cervical) lymphadenopathy is often reported as the next most common site of disease in adults, it has infrequently been reported in adolescents. Up to 4% of adolescents in two series had tuberculous meningitis, 11,16 although this may be explained by selection bias resulting from those with more severe forms of tuberculosis being more likely to be identified and correctly diagnosed.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the major sites of disease and prevalence of confirmed disease in case series of adolescents with tuberculosis identified during this review. 10-12, [14][15][16][17][18][19][20][21][22][23][24] While peripheral (most commonly cervical) lymphadenopathy is often reported as the next most common site of disease in adults, it has infrequently been reported in adolescents. Up to 4% of adolescents in two series had tuberculous meningitis, 11,16 although this may be explained by selection bias resulting from those with more severe forms of tuberculosis being more likely to be identified and correctly diagnosed.…”
Section: Figurementioning
confidence: 99%
“…26 Adolescents with pulmonary tuberculosis commonly have "bacteriologically confirmed" disease (i.e. smear, culture or PCR positive), [9][10][11]16,19,26 although paucibacillary disease remains common and negative test results do not rule out tuberculosis. Yields from multiple samples (usually two) collected on the same day have been shown to be similar to samples collected on separate days in children, potentially making sample collection less burdensome and more feasible.…”
Section: Figurementioning
confidence: 99%
“…The most commonly reported symptoms were coughing (55.9%), fever (46.9%), and weight loss (37.9%), which were also described as the main symptoms in similar cohorts. 12 , 13 , 14 The occurrence of these symptoms were correlated with age: they were more present in the group of children over 10 years of age. The low frequency of these symptoms in the patients younger than 10 years of age and the oligosymptomatic nature of TB in this age group reinforce the difficulty of diagnosing the disease in younger children.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to our study, Lotfian et al reported on outcomes of adolescent TB patients in Iran and did not find differences in loss- to-follow-up between younger and older adolescents. However the small sample size of that study precluded investigators from performing the statistical modelling required to identify independent risk factors for loss-to-follow up [26]. In addition, a study in India found no loss to follow-up in their sample of young people in TB care, but here too the small sample size of the study, in comparison to the large adolescent population at risk of TB disease in that country, means the findings are unlikely to be generalizable[27].…”
Section: Discussionmentioning
confidence: 99%